JERICA SNOJ: METAFORA V LEKSIKALNEM SISTEMU: Ljubljana: Založba ZRC, ZRC SAZU, 2010. (Zbirka Linguistica et philologica, 24). 213 str. - Voršič, Ines (Slavia Centralis, 2020)
Review: Jerica Snoj: Metafora v leksikalnem sistemu The author presents the scientific monograph by Jerica Snoj, Metafora v leksikalnem sistemu (Metaphor in the Lexical System), published in 2010.